TRANSFORMATIVE PEDAGOGY IN BUILDING EQUITABLE ACCESS TO NATIONAL EDUCATION - Nurhayati, Ifa; Mo’tasim, Mo’tasim; Mustafa, Sahidi; Tazali, Imam (Jurnal Konseling Pendidikan Islam, 2025)
This research aims to analyze the role of transformative pedagogy in building equitable access to national education in Indonesia. Transformative pedagogy, rooted in the thought of Paulo Freire, emphasizes education as a liberatory process that fosters critical consciousness and social justice. This research uses a qualitative approach with a descriptive-analytical design, through document analysis of national education policies, in-depth interviews with teachers, principals and education office officials, and triangulation of data from various sources. The data were analyzed using thematic analysis techniques with reference to Critical Pedagogy theory (Freire, 1970) and Social Justice Theory (Rawls, 1971). The results show that national policies such as Merdeka Belajar have reflected the spirit of inclusiveness, but have not fully realized the transformation of social awareness in educational practice. Teachers have not played an optimal role as agents of change because the education system is still hierarchical and oriented towards academic achievement. This research concludes that equal access to education can only be realized through the synergy between social justice policy reform and the application of liberating transformative pedagogy. The integration of the two is an important foundation for an inclusive, humanist and transformative national education.